Coach-created motivational climate ratings differentiate between dropout and continuation in Australian youth swimming - Moulds, K.; Fraser, K. K.; Karp, J.; Kapocius, O.; Heathcote, M.; Appleton, P. R.; Cobley, S. (International Journal of Sports Science & Coaching, 2023)
Objectives Applying Bronfenbrenner's Bio-Ecological Systems Theory and PPCT model recommendations, this study examined whether specific or multiple factors were associated with participation status in Australian youth swimming; a context known for high dropout rates.